ANALISIS KETERAMPILAN MENGAJAR GURU IPA DI MTs THAMRIN YAHYA KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU TAHUN PEMBELAJARAN 2015/2016 - Yanti, Lisa (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This study aims to know skill of teacher science in MTs Thamrin Yahya RambahHilir Rokan Hulu. The population and sample in study it is a whole science teacher MTs Thamrin Yahya Kecamatan Rambah Hilir Rokan Hulu recency collected by the way of chief . The results of the analysis data of skills open and close lessons to the percentage average 81,67 % , skill explain lessons to the percentage average 81,67 % , skill ask with the percentage average 83,33 % , skill hold variation by the percentage average 64,92 %, skill manage class with the average 70,00 % , skill manage small group with the average 80,00 % , skill give strengthening with the average 81,67 % , and latest skill teaching individuals with the percentage flattened with average 65,00 %, to regency got the final average score 76,03 % good categorized.